Thinking Arabic translation a course in translation method : Arabic to English - Dickins, J. (James); Hervey, Sándor G. J.; Higgins, Ian (Routledge, 2017)
"Thinking Arabic Translation is an indispensable book for linguists who want to develop their Arabic-to-English translation skills. Clear explanations, discussions, examples and exercises enable students to acquire the skills necessary for tackling a broad range of translation problems. The book has a practical orientation, addressing key issues for translators such as cultural differences, genre, and revision and editing. It is a book on translation method, drawing on a range of notions from linguistics and translation theory to encourage thoughtful consideration of possible solutions to practical problems. This new edition includes: - new and up-to-date examples from all types of translation, covering broad issues that have emerged in the Arab world in recent years - texts drawn from a wide variety of writing types, including newspapers, prose fiction, poetry, constitutions and political speeches - at least 3 full-length practical translation exercises in each chapter to compliment the discussions and consolidate learning. Thinking Arabic Translation is key reading for advanced students wishing to perfect their language skills or considering a career in translation."